Characterizing complex opioid use disorder care trajectories and outcomes following acute service utilization: A protocol for a population-based data linkage study - Noa Krawczyk; Ignacio Bórquez; Megan Miller; Sung Woo Lim; Teena Cherian; Daniel Schatz; Alex Harocopos; Emily Carter; Marc Scott; Brandy F. Henry; David Frank; Magdalena Cerdá; et al. (PLoS ONE, 2026)
Despite robust evidence that medications for opioid use disorder (MOUD) reduce overdose and mortality, substantial care gaps remain following opioid-related hospital encounters. The opioid use disorder (OUD) Cascade of Care framework conceptualizes progression from identification to treatment initiation and retention, yet limited research has examined how real-world OUD treatment trajectories unfold, particularly across treatment episodes and multiple care settings. This paper describes an NIH-funded study protocol (1R01DA061367-01A1) to conduct a longitudinal observational study using linked administrative data across New York City to characterize OUD treatment trajectories following opioid-related hospital encounters. Using the OUD Cascade of Care framework, we will apply state sequence analysis to identify common patterns of OUD treatment engagement in the year following hospitalization, including transitions between treatment modalities and periods in and out of care. We will examine how care trajectories vary by individual and neighborhood characteristics, and assess associations between trajectories and key outcomes, including rehospitalization, overdose, and mortality. By applying novel data-driven longitudinal methods, this study will advance understanding of the complex, non-linear nature of OUD treatment engagement. Findings will inform health system and policy efforts to identify populations at elevated risk, hospital-based interventions, and opportunities to address gaps in care to reduce overdose-related harms.